PENGARUH SEGMENTASI DAN POSITIONING TERHADAP KEPUTUSAN PEMBELIAN WISATAWAN PADA RUMAH MAKAN - Iis Indriyarti D Kiwang; Apriana H J Fanggidae; Rolland E Fanggidae (Universitas Nusa Cendana, 2019)
This research is explanatory research to explain the effect of segmentation and positioning ontourists' purchasing decisions on Rumah Makan Ayam Bakar Wong Solo Kupang. The variablesin this study are as follows: Independent Variables ; Segmentation (X1), Positioning (X2), andDependent Variable ; Purchase Decision (Y). The population of this study were tourists who boughtin Rumah Makan Ayam Bakar Wong Solo Kupang, with a sample of 97 respondents taken bypurposive sampling. Data collection techniques in this study used questionnaire and observationmethods. Test of the instrument using validity test, classical assumption test, and reliability test,and hypothesis testing using t test and f test. Data analysis techniques used descriptive statistics,multiple linear regression, and coefficient of determination. The data obtained is processed using theSPSS 20.0 for program. Keywords: Segmentation, Positioning, Purchasing Decisions